APEX-MODFLOW: A New integrated model to simulate hydrological processes in watershed systems. (September 2021) - Bailey, Ryan T.; Tasdighi, Ali; Park, Seonggyu; Tavakoli-Kivi, Saman; Abitew, Tadesse; Jeong, Jaehak; Green, Colleen H.M.; Worqlul, Abeyou W.
Abstract: APEX (A gricultural P olicy/E nvironmental eX tender) is an oft-used agroecosystem model but has limited use in groundwater-driven watersheds due to a simplistic representation of groundwater processes. This paper presents the linkage of APEX and the groundwater flow model MODFLOW into a single modeling code. The mapping of recharge, groundwater head, and groundwater-surface water interactions are handled internally via subroutines. The APEX-MODFLOW model is applied to three watersheds in the United States for testing code accuracy and hydrologic state variables and fluxes: the Animas River Watershed, Colorado and New Mexico (3543 km 2 ); the Price River Watershed, Utah (4886 km 2 ); and the Middle Bosque River Watershed, Texas (470 km 2 ). Whereas the hydrology of the Animas River and Price River watersheds is driven by snowmelt and spring runoff, the hydrology of the Middle Bosque River Watershed is driven by summer thunderstorms. The model can be used for scenario analysis in groundwater-driven watersheds. Highlights: New integrated hydrologic model links APEX model to MODFLOW model. Model passes recharge, water table elevation, and gw-sw flux rates internally. APEX-MODFLOW applied to three watersheds in Utah, Colorado, and Texas, USA. Model results show importance of including physically based groundwater flow.